1996
DOI: 10.1002/(sici)1521-186x(1996)17:6<483::aid-bem8>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental dosimetry of petri dish exposure setups

Abstract: Crawford TEM cells are often used to expose cell cultures or small animals in order to study the effects caused by high-frequency fields. They are self-contained, easy-to-use setups that provide a rather homogeneous field distribution in a large area around its center, corresponding approximately to far-field conditions. However, a number of conditions must be met if such TEM cells are intended to be used for in vitro experiments. For instance, poor interaction with the incident field must be maintained to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 2 publications
3
27
0
Order By: Relevance
“…The expected SAR profile was guided by the analysis presented in (Burkhardt et al 1996). In an idealised set-up (where the geometry can be simplified to that of a thin horizontal conductive sheet subject to an E-field that is vertically polarised), the authors derive analytical formulae that suggest the SAR is highest at the bottom and top of the Petri dish, and uniform in the horizontal direction.…”
Section: Rf Exposure and Dosimetrysupporting
confidence: 89%
See 2 more Smart Citations
“…The expected SAR profile was guided by the analysis presented in (Burkhardt et al 1996). In an idealised set-up (where the geometry can be simplified to that of a thin horizontal conductive sheet subject to an E-field that is vertically polarised), the authors derive analytical formulae that suggest the SAR is highest at the bottom and top of the Petri dish, and uniform in the horizontal direction.…”
Section: Rf Exposure and Dosimetrysupporting
confidence: 89%
“…Figure 1 highlights the uniformity of SAR in the bottom layer where the bones lie. This is in line with the theoretical approach of (Burkhardt et al 1996), where, the SAR profile is uniform in the horizontal direction (apart from near the sides of the dish), and highest at the top and the bottom. Due to the uniformity of SAR distribution along the bottom of the dish, the precise positioning of the bones on the bottom layer was not critical.…”
Section: In Vitro Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The cells, which intially float in the medium, line down on the bottom of the petri disk in a few minutes. For this reason the attenuation of field at the bottom of the petri dish used can be ignored since it has been calculated to be less than 2% (Burkhardt et al, 1996). The medium was always pre‐heated at 37°C in order to avoid the temperature raise time and the stress to the cells.…”
Section: Methodsmentioning
confidence: 99%
“…4A. Medium volume is an important parameter because eddy currents (and hence SAR) are expected to increase quadratically with medium height [Burkhardt et al, 1996;Staff, 1943], while thermal diffusion affects the plateau linearly with increasing thickness. Numerical simulations revealed that thermal diffusion effects should have become steady with medium volumes of Շ40 ml.…”
Section: Thermalmentioning
confidence: 99%